Analysis of Traffic Accidents in the Area of Small Towns in the Republic of Croatia - Vinko Višnjić; Marko Pušić (Promet (Zagreb), 2009)
The safety of road traffic in small towns in the Republic of Croatia is not at a satisfactory level. As proof, the safety of road traffic participants in the area of the town of Nova Gradiška and its wider environment has been studied and analyzed. The paper includes the available data in the period from 2000 to 2007. The analysis and the assessment of road traffic safety can be applied also to other towns and counties of the Republic of Croatia. Having in mind that there are 531 settlements in the Republic of Croatia (119 towns and 412 districts), out of which only 78 are larger than 10,000 inhabitants or 14.69% of the total number, which means that the analysis could be made for any settlement in the Republic of Croatia. The road traffic safety assessment was conceived according to the modified Smeed model which may be applied for any settlement or town. The road traffic safety analysis has led to the conclusion that safety of all the traffic participants is endangered. This paper provides solutions about what has to be done in order to reduce the danger to all the road traffic factors. KEY WORDS: drivers, traffic, traffic accidents, safety and small towns